The prevalence and socioeconomic correlates of depressive and anxiety symptoms in a group of 1,940 Serbian university students - Simić-Vukomanović, Ivana; Mihajlović, Goran; Kocić, Sanja; Djonović, Nela; Banković, Dragić; Vukomanović, Vladimir; Djukić-Dejanović, Slavica (Vojnosanitetski pregled, 2017)
Background/Aim. Mental health of university students is under increasing concern worldwide, because they face challenges which predisposes them to depression and anxiety. The aim of this study was to identify demographic and socioeconomic variables associated with depressive and anxiety symptoms among university students. Methods. This cross-sectional study on 1,940 university students was performed using a questionnaire including demographic and socioeconomic variables, Beck Depression Inventory and Beck Anxiety Inventory. Results. The prevalence of depressive symptoms in students was 23.6%, while the prevalence of anxiety symptoms was 33.5%. The depressive symptoms were significantly related to the study year (p = 0.002), type of faculty (p = 0.014), satisfaction with college major choice (p < 0.001), satisfaction with grade point average (p < 0.001). Female students (odds ratio – OR = 1.791, 95% confidence interval – CI = 1.351–2.374), older students (OR = 1.110, 95% CI = 1.051-1.172), students who reported low family economic situation (OR = 2.091, 95% CI = 1.383–3.162), not owning the room (OR = 1.512, 95% CI = 1.103–2.074), dissatisfaction with graduate education (OR = 1.537, 95% CI = 1.165–2.027) were more likely to show depressive symptoms. The anxiety symptoms were significantly related to study year (p = 0.034), type of faculty (p < 0.001), family economic situation (p = 0.011), college residence (p = 0.001) satisfaction with the college major choice (p = 0.001), and satisfaction with graduate education (p < 0.001). Female students (OR = 1.901, 95% CI = 1.490–2.425), and students who reported parents high expectations of academic success (OR = 1.290, 95% CI = 1.022–1.630) were more likely to show anxiety symptoms. Conclusion. This is one of the largest study examining mental disorders in a sample of university students in Serbia. These findings underscore the importance of early detections of mental problems and prevention interventions in university students.